English teachers’ beliefs about communicative competence and their relationship with their classroom practices (2008)
This article describes a research project conducted with two English Teachers from the Extension Program at Foreign Language Department, National University in Bogotá. The purpose of the study was to establish the relationship between what English teachers understand on communicative competence and what they actually do in their English classes. The teachers were observed during 4 months, and they were also interviewed. The findings show how hard it is to define what communicative competence is in teachers’ own words. Data also show how important students are in the English classrooms. English teachers should make careful decisions to help themdevelop their language competence. Key words: Communicative competence, English teacher’s beliefs and reflections, classroom practices, English students’ roles, decision making Este artículo describe un proyecto de investigación llevado a cabo con dos profesores de inglés de la Unidad de Extensión del Departamento de Lenguas Extranjeras de la Universidad Nacional de Colombia, en Bogotá. El estudio tenía como objetivo establecer la relación entre lo que los profesores comprenden sobre la competencia comunicativa y lo que ellos realmente hacen en el salón de clase. Los profesores fueron observados por un período de cuatro meses y también fueron entrevistados. Los resultados del estudio muestran lo complejo que resulta para los profesores definir la competencia comunicativa en sus propias palabras. También es posible evidenciar la importancia que los estudiantes tienen en el salón de clase de inglés. Los profesores de inglés deben ser cuidadosos al momento de tomar decisiones con el fin de ayudar a los estudiantes a desarrollar su competencia en la lengua extranjera. Palabras clave: Competencia comunicativa, creencias y reflexiones de los profesores de inglés, prácticas de clase, roles de los estudiantes de inglés, toma de decisiones